2016
DOI: 10.1097/gme.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters among MsFLASH clinical trial participants

Abstract: Objective Women experience multiple co-occurring symptoms (symptom clusters) during the menopausal transition and early postmenopause. Although symptom clusters have been identified among community-dwelling midlife women, to date there have been no studies of midlife participants in clinical trials for hot flashes. Our objective was to identify symptom clusters using standardized measures completed by participants in the Menopausal Strategies: Finding Lasting Answers to Symptoms and Health (MsFLASH) clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…The links between frequent, severe, or bothersome VMS and sleep problems, 44, 45 mood problems, 4649 and concentration difficulties 50, 51 have all been previously documented and are consistent with two previously published MsFLASH reports: MsFLASH trial participants’ symptom priorities 52 and symptom clusters. 53 In MsFLASH 02, a companion study was added and it required trial participants to complete a card sort task to indicate which three of twelve possible symptoms they would most like to alleviate. 52 The four most highly rated symptoms were VMS, sleep disruption, concentration impairment, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The links between frequent, severe, or bothersome VMS and sleep problems, 44, 45 mood problems, 4649 and concentration difficulties 50, 51 have all been previously documented and are consistent with two previously published MsFLASH reports: MsFLASH trial participants’ symptom priorities 52 and symptom clusters. 53 In MsFLASH 02, a companion study was added and it required trial participants to complete a card sort task to indicate which three of twelve possible symptoms they would most like to alleviate. 52 The four most highly rated symptoms were VMS, sleep disruption, concentration impairment, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using pooled data across the MsFLASH trials (n=899), five classes of symptom clusters were found. 53 The classes were: (1) hot flash interference, sleep problems, and pain, (2) hot flash interference, sleep problems, mood problems, and pain, (3) hot flash interference and sleep problems, (4) hot flash interference and mood problems, and (5) low severity of all symptoms. Problems with concentration were not measured as a MsFLASH outcome for use in the clusters analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Women were less likely to be in either of the two latent classes that included hot flashes when they were premenopausal. In the MsFLASH clinical trial, latent class analysis based on hot flash, insomnia, sleep, depressed mood, anxiety and pain symptoms identified 5 classes, 4 of which included hot flashes [ 12 ]. Mishra and Dobson [ 13 ] conducted factor analysis to identify symptom clusters of 17 general health and menopausal symptoms using data from the Australian Longitudinal Study of Women’s Health (ALSWH).…”
Section: Introductionmentioning
confidence: 99%
“…Im and colleagues [ 17 ] reported race/ethnic differences in reporting of the number and severity of physical symptoms but only in the least symptomatic cluster. The MS-Flash study reported that Black women were more likely than White women to cluster in the severe hot flash, insomnia and pain cluster [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep complaints are a common and often bothersome menopausal symptom 1,2 which increase throughout the menopausal transition and early postmenopause. 3,4 Insomnia is associated with increased depression, impaired daytime function, reduced libido, and increased health care utilization, creating a substantial burden for women and society.…”
Section: Introductionmentioning
confidence: 99%